Patients' perspectives of endometriosis-related fatigue: qualitative interviews - Dana DiBenedetti; Ahmed M. Soliman; Catherine Gupta; Eric S. Surrey (SpringerOpen, 2020)
Abstract Background Endometriosis-related fatigue is common and negatively impacts multiple areas of many women's lives, particularly in day-to-day activities, social activities, physical activities, mood and emotions, relationships with family or partners, and work or school. Multiple studies have documented fatigue as a significant symptom of endometriosis. Additional research is needed to better understand endometriosis-related fatigue and its impacts on patients. Methods This qualitative study consisted of individual in-person semistructured interviews conducted with 22 adult females reporting moderate to severe endometriosis-related pain. Women with self-reported, surgically confirmed endometriosis and moderate to severe endometriosis-related pain were recruited from qualitative research firms in two locations in the United States. Qualified subjects participated in semistructured interviews that lasted approximately 45 min each. Interviews were audio recorded and transcribed for qualitative analysis. Results All 22 participants reported experiencing fatigue related to their endometriosis. While the degree of severity of their endometriosis-related fatigue varied, 21 of the 22 participants stated that it was at least "somewhat bothersome." Most participants noted an impact from endometriosis-related fatigue on day-to-day activities, social activities, physical activities, mood and emotions, relationships with family or partner, and work or school. Conclusions The data presented here indicate that endometriosis-related fatigue has a pervasive impact on the functioning of women living with this condition. Future studies should measure any changes in fatigue that may be associated with treatment for endometriosis.